The VSE Refinement Method in Hets - Mossakowski, Till; Codescu, Mihai; Maeder, Christian; Langenstein, Bruno (Electronic Communications of the EASST, 2013)
We present the integration of the refinement method of the VSE verification tool, successfully used in industrial applications, in the Heterogeneous Tool Set Hets. The connection is done via introducing the dynamic logic underlying VSE and two logic translations in the logic graph of Hets. Thus the proof management formalism provided by Hets can be applied for VSE specifications without modification of the logic independent layers of Hets.